The Impact of Green HRM, Leadership, Innovation, and Psychological Climate on Business Sustainability - Sari Fitri; Rahmad Ade Putra; Muhlisah Lubis (Annals of Human Resource Management Research, 2026)
Purpose: This study aims to analyze the effects of Green Human Resource Management, Green Transformational Leadership, and Green Innovation on Business Sustainability, with Green Psychological Climate as a mediating variable among Forest Farmer Groups under the guidance of the Pasaman Raya Protected Forest Management Unit. Research Methodology: This study employed a quantitative survey method involving 200 members of Forest Farmer Groups actively engaged in Kelulut Honey cultivation in Pasaman Raya, Indonesia. Data were collected using structured questionnaires and analyzed using PLS-SEM with SmartPLS software. Results: The findings show that Green Human Resource Management, Green Transformational Leadership, and Green Innovation positively and significantly impact Business Sustainability and Green Psychological Climate. Additionally, Green Psychological Climate significantly mediated the relationships between these factors and Business Sustainability. Conclusions: This study concludes that effective green management practices, environmentally oriented leadership, and continuous green innovation are essential for strengthening psychological support for pro-environmental behavior, which ultimately enhances business sustainability in community-based organizations. Limitations: This study was limited to Forest Farmer Groups in Pasaman Raya and focused on Kelulut honey cultivation, which may restrict the generalization of the findings to other sectors and regions. Contributions: This study provides empirical evidence of how green practices and leadership promote sustainability, contributing to sustainable management, environmental psychology, and community-based business development. The findings offer valuable insights for policymakers, community leaders, and development agencies aiming to support sustainable business models in rural and environmental organizations in Indonesia.